Incidence and predictors of pericardial effusion following surgical closure of atrial septal defect in children: A single center experience - Campisano, Martina; Celani, Camilla; Franceschini, Alessio; Pires Marafon, Denise; Federici, Silvia; Brancaccio, Gianluca; Galletti, Lorenzo; De Benedetti, Fabrizio; Chinali, Marcello; Insalaco, Antonella (Frontiers in Pediatrics, 2022)
OBJECTIVES: To evaluate the incidence of pericardial effusion (PE) after surgical atrial septal defect (ASD) closure and to investigate the presence of predictive risk factors for its development. METHODS: We collected data of 203 patients followed at Bambino Gesù Children’s Hospital of Rome who underwent cardiac surgery for ASD correction between January 2015 and September 2019. RESULTS: A total of 200/203 patients with different types of ASD were included. Patients were divided in two groups: group 1, 38 (19%) who developed pericardial effusion (PE) and group 2, 162 (81%) without PE. No differences were noted between the two groups with regards to gender or age at the surgery. Fever in the 48 hours after surgery was significantly more frequent in group 1 than in group 2 (23.7% vs 2.5%; p<0.0001). ECG at discharge showed significantly ST segment elevation in children who developed PE, 24.3% vs 2.0% in those who did not (p<0.0001). Group 1 patients were divided in two subgroups on the basis of the severity of PE: 31 (81.6%) with mild and 7 (18.4%) with moderate/severe PE. Patients with moderate/severe PE had a significative higher BMI value (median 19.1 Kg/m2) (range 15.9-23.4, p=0.004) CONCLUSIONS: Presence of fever and ST segment elevation after surgery predict subsequent development of PE suggesting a closer follow-up for this categories of patients. A higher BMI appears to be associated to a higher risk of moderate/severe PE.